Understanding the influence of farmer motivations on changes to soil erosion risk on sites of former serious erosion in the South Downs National Park, UK - Boardman, J.; Bateman, S.; Seymour, Susanne (Elsevier, 2017)
Serious soil erosion occurred in the South Downs National Park, southern England in the years 1982–2006 and details of around 400 sites are contained in a database. In 2010 we revisited 85 of the most serious sites where erosion of >10 m3 ha−1 y−1 had been recorded in order to assess land use change and any conservation measures undertaken. At 79% of the sites land use change had resulted in a reduction in the risk of erosion, most notably at 28 sites with a shift to permanent grass from winter cereals. At only 21% of sites was the risk of erosion unchanged. Twenty two farmers responsible for 66 of the sites were interviewed. Land management practices had changed on all of the fields of interest to this study since the time of the serious erosion events, to those which have the potential to lower soil erosion risk. Sixteen interviewees claimed that erosion was a motivating reason for changing their practices, due to either experiencing on or on- and off-farm impacts firsthand (12), having knowledge or suspicion of serious erosion having occurred on their land prior to their management (three), or having no knowledge of any serious erosion on their land but just wanting to reduce overall erosion risk (one). Amongst the main changes reported are changes of land use from winter cereals to grass or to overwinter stubble which have undoubtedly reduced the risk of erosion. However, some changed practices claimed by farmers, such as along-the-contour-working, earlier sowing and the use of rollers may be of little value. Furthermore, deeper analysis of farmers’ motivations regarding changes in land management practices suggests a complex picture in which a range of socio-economic influences come into play over time including financial incentives offered by agri-environmental schemes which were found to be an important driver of change. Future changes in farming economics may therefore undermine the reduction in erosion risk in the longer term.